The Comparison of Lexical Bundles in Conversation Texts between Four Corners and English Intensive Course Books - Aini, Nurma; Faridi, Abdurrachman; Fitriati, Sri Wuli (English Education Journal, 2018)
Lexical bundle is a word combinations that usually hangs together. By identifying the lexical bundles, we can see what native usually say and or write in certain register. Therefore, the identification the lexical bundles would indicate to what extend the speaker speak native-like. The objectives of the study are (1) to compare the lexical bundles’ frequencies in conversation texts between Four Corners and English Intensive Course books, (2) to compare the lexical bundles’ structures in conversation texts between Four Corners and English Intensive Course books, (3) to compare the lexical bundles’ functions in conversation texts books between Four Corners and English Intensive Course books. This study is a corpus study. The data are the conversation texts which existed in two textbooks; Four Corners with native authors and English Intensive Course with non-native authors. The result revealed that (1) the frequency of lexical bundles in Four Corners are higher than in English Intensive Course books, (2) both Four Corners and English Intensive Course books more frequent in using lexical bundle that incorporate verb phrase fragments, (3) the dominant function of lexical bundles used in two textbooks are special function, most of them consist of simply inquiry. Theoretically, this research contributes to other researchers as a building block for its literature contribution in their review in the case of the similarity and the difference of the lexical bundles’ frequencies, structures, and functions.